Investigating the direct and indirect environmental pressures of New Zealand's food and fibre industries. (23rd April 2008) - Andrew, Robbie; Forgie, Vicky
The production and processing of primary products has been the foundation of the New Zealand economy for 150 years. However, the economic benefit gained from the food and fibre industries has come with associated environmental costs. While the producer-centric approach is the prevalent way of viewing environmental pressures from production, consumption decisions also have an influence on environmental outcomes. From a production perspective, the food and fibre industries analysed herein together appropriated approximately 30% of New Zealand's energy, 88% of economically available land, and 46% of the nation's total potential. When environmental pressures are assigned by consumption categories, households in New Zealand appropriated 24% of land used in domestic production, 52% of energy, and 43% of GWP. Exports appropriated 67% of land use, 35% of energy, and 52% of GWP. The remainders were appropriated by Other Final Demand.